Avaliação da sobrevida segundo o estado nutricional de pacientes com câncer do aparelho digestório - Barão, Katia [UNIFESP] (2016)
Objective: To evaluate survival according to the nutritional status of patients with tumors of the digestive system in remission or active, based on body mass index, the subjective global assessment produced by the patient and the phase angle, with nutritional counseling, and / or use supplements. Methods: We included patients treated from gastro-oncology outpatient nutrition team Unifesp/EPM. Patients were compared with cancer remission (Clinical Follow-up Group) or active (Cancer Group); with nutritional counseling (G1) or with nutritional supplementation and counseling (G2). All patients underwent PG-SGA, BMI and phase angle (PA). Results: 673 patients, the cancer group represented 40% of the sample. The mean age was 62.2 ± 12.4 years, with 53% of men. The CRC represented 61% gastric 19% esophageal 10% bile ducts, liver and pancreas (CBLP) 6% and 4% excluded. The stage IV was prevalent (37%), followed by stage III (24%). In the first assesment, 59% had PG-SGA B. The average PA was 5.1 ± 1.1. Patients with CBLP had the lowest median survival. Well nourished patients lived four times longer than the severely malnourished. Just PG-SGA C and PA ?5º, were confirmed as prognostic markers. G1 patients had a significant increase in the score of the PG-SGA (P <0.01) and decreased PA (p = 0.03). Conclusions: Malnutrition negatively influenced survival despite the remission of the disease. Cancer Group Patients, Anabolic or at malnutrition risk had lower survival. The relative risk of death was five times higher in severely malnourished patients and twice in patients with PA ?5º. PG-SGA has shown that most patients had moderate or severe malnutrition before starting the cancer treatment. Nutritional supplementation did not affect the survival or reverse malnutrition in advanced stage patients, but managed to contain the progressive weight loss. The group without supplementation presented clinical decrease with the reduction of PA and higher scores of PG-SGA, suggesting that supplementation may be beneficial for advanced stages patients even without reverse malnutrition